2013
DOI: 10.1128/jvi.00577-13
|View full text |Cite
|
Sign up to set email alerts
|

The L60V Variation in Hepatitis B Virus Core Protein Elicits New Epitope-Specific Cytotoxic T Lymphocytes and Enhances Viral Replication

Abstract: Mutations in the core protein (HBc) of hepatitis B virus (HBV) are associated with aggressive hepatitis and advanced liver diseases in chronic hepatitis B (CHB). In this study, we identified the L60V variation in HBc that generates a new HLA-A2-restricted CD8 ؉ T cell epitope by screening an overlapping 9-mer peptide pool covering HBc and its variants. The nonameric epitope V60 was determined by structural and immunogenic analysis. The HBc L60V variation is correlated with hepatic necroinflammation and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…and ; Supporting Fig. S3) . We also showed that the HCC‐associated mutant BCP/PC/2051 triggered inflammation and fibrosis in the human hepatocyte chimeric mouse model related to increased levels of genes that have been associated with HCC and/or cell proliferation.…”
Section: Discussionsupporting
confidence: 52%
“…and ; Supporting Fig. S3) . We also showed that the HCC‐associated mutant BCP/PC/2051 triggered inflammation and fibrosis in the human hepatocyte chimeric mouse model related to increased levels of genes that have been associated with HCC and/or cell proliferation.…”
Section: Discussionsupporting
confidence: 52%
“…HBx, HBs and HBc could integrate with human genes to influence patient survival3940. In addition, hot spot mutations in HBc (L60V, S87G and I97L) can affect HBV replication, viral persistence, and immunopathogenesis during chronic viral infection4142. Thus, we are preparing to integrate the genomics data and transcriptomics data to study the role of HBc in the HBV-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the preC/C region is abundant with epitopes of both B cells and T cells, which are critical for host immunity to clear virus (24,27); mutations in this region are associated with advanced liver diseases, including severe and fulminant hepatitis B, cirrhosis, and hepatocellular car- (22) cinoma (33)(34)(35). HBV could evolve by mutations and indels to increase its adaptation against environmental selection, and these mutations manifest as escaping from host immunity to survival or lowering the binding affinity of epitopes to lymphocytes (36). Nucleotide substitution rates or evolution rates of full-length HBV were 7.9 ϫ 10 Ϫ5 substitutions/site/year as reported by Osiowy et al (37), which was slightly higher than previously published estimates (1.5 ϫ 10 Ϫ5 to 5 ϫ 10 Ϫ5 substitutions/site/year) (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%